The nonlinear impact of heterogeneous environmental regulations on corporate carbon emissions: a perspective based on internal and external governance - Li, Dongsheng; Li, Yue; Liu, Keminhui; Liu, Dan (Frontiers in Earth Science, 2025)
IntroductionEnvironmental regulation is a vital mechanism for promoting environmental protection and sustainable development, as well as a key factor in driving enterprise transformation, modernization, and enhanced competitiveness.MethodTo understand how heterogeneous environmental regulations interact with corporate governance structures to influence emission outcomes is critically important. This study analyzes Chinese A-share manufacturing listed companies from 2015 to 2022, categorizing environmental regulations into three types: command-and-control, market-based incentives, and public participation. It investigates the impacts of these regulations on corporate carbon emissions and explores the moderating effects of internal control quality and marketization from the perspectives of internal and external corporate governance.ResultsThe findings indicate that: (1) The impacts of command-and-control and market-based incentive regulations on corporate carbon emissions follow an inverted U-shape, while public participation regulations demonstrate a U-shape. (2) Marketization has strengthened the impact of all three types of environmental regulations on corporate carbon emissions, while the quality of internal control only moderates the influence of command-and-control and market-based incentive regulations, without having an impact on public-participatory environmental regulations. (3) The emission reduction effects of heterogeneous environmental regulations are more pronounced in enterprises with high ESG performance, low financing constraints, and those in growth or maturity stages.ConclusionThis study provides empirical evidence for governments to implement targeted policies and for enterprises to effectively reduce emissions, contributing to the optimization of environmental regulation policies and the sustainable development of businesses.